Exome sequencing reveals NAA15 and PUF60 as candidate genes associated with intellectual disability. Issue 1 (9th October 2017) - Zhao, Jin J.; Halvardson, Jonatan; Zander, Cecilia S.; Zaghlool, Ammar; Georgii‐Hemming, Patrik; Månsson, Else; Brandberg, Göran; Sävmarker, Helena E.; Frykholm, Carina; Kuchinskaya, Ekaterina; Thuresson, Ann‐Charlotte; Feuk, Lars
Abstract : Intellectual Disability (ID) is a clinically heterogeneous condition that affects 2–3% of population worldwide. In recent years, exome sequencing has been a successful strategy for studies of genetic causes of ID, providing a growing list of both candidate and validated ID genes. In this study, exome sequencing was performed on 28 ID patients in 27 patient‐parent trios with the aim to identify de novo variants (DNVs) in known and novel ID associated genes. We report the identification of 25 DNVs out of which five were classified as pathogenic or likely pathogenic. Among these, a two base pair deletion was identified in the PUF60 gene, which is one of three genes in the critical region of the 8q24.3 microdeletion syndrome (Verheij syndrome). Our result adds to the growing evidence that PUF60 is responsible for the majority of the symptoms reported for carriers of a microdeletion across this region. We also report variants in several genes previously not associated with ID, including a de novo missense variant in NAA15. We highlight NAA15 as a novel candidate ID gene based on the vital role of NAA15 in the generation and differentiation of neurons in neonatal brain, the fact that the gene is highly intolerant to loss of function and coding variation, and previously reported DNVs in neurodevelopmental disorders.